Creación de una consultoría contable y tributaria para el sector microempresarial en la ciudad de ventanas, año 2011. - García Zambrano, Pedro Julio (2012)
The accounting and tax consultancy "CONTRISERVICIOS GARCÍA" worked in the commercial sector windows downtown Canton street and Bolivar November 10 which will feature modern technological equipment and appropriate to provide a good service to microentrepreneurs in the agricultural, livestock services and others, advice on accounting, tax, transactional filing attachments, obtaining the RUC, preparation of financial statements, etc.. Financing is what you get with equity and financed by a bank in the town of Windows that will allow you to cover all the services offered and services meet the 75% unmet demand microentrepreneurs. According to neo economic calculations accounting requires an initial investment of USD 11 414, 73 of which USD 7980.74 correspond to fixed assets and USD 2890.43 correspond to operating capital estimated at 5% for contingencies is of USD 543.56. Estimates for the total projected expenditures for the first year is $ 28,034.68, and total revenue for the first year is $ 32,175.00, representing the year 1, and for the first year is obtained income of USD3579, 13ctv, cost = profit 0.15ctv equal, which means that the project is viable, the NPV is $ 21,618.38 and the IRR is 98%.